Staging Doubt Skepticism in Early Modern European Drama - Pawlita, Leonie (De Gruyter, 2019)
This volume considers the influential revival of ancient philosophical skepticism in the 16th and early 17th centuries and investigates, from a comparative perspective, its reception in early modern English, Spanish and French drama, dedicating detailed readings to plays by Shakespeare, Calderón, Lope de Vega, Rotrou, Desfontaines, and Cervantes.